CLINICAL CHARACTERISTICS OF ANKYLOSING SPONDYLITIS IN REAL PRACTICE IN RUSSIA: RESULTS OF THE CROSS-SECTIONAL NON-INTERVENTIONAL TRIAL EPICA2 - Sh. F. Erdes; T. V. Dubinina; D. E. Abdulganieva; I. B. Vinogradova; L. P. Evstigneeva; A. V. Elonakov; E. N. Otteva; T. A. Raskina; T. S. Salnikova; R. R. Samigullina; V. N. Sorotskaya; L. M. Shkil (Научно-практическая ревматология)
The literature virtually lacks the results of investigations aimed to study the clinical picture of ankylosing spondylitis (AS) in the real practice of rheumatologists  in Russia. At the same time, these investigations may give information  on not only the epidemiological aspects of the disease, but also a variety of its clinical presentation, its social importance, allow evaluation of the efficiency of therapy, and plan a system of further health care costs.Subjects and methods. In early 2015, the cross-sectional multicenter  non-interventional trial EPICA2 was conducted to refine the clinical picture of AS in the real practice of a rheumatologist. The trial involved 402 patients with AS from 10 centers of Russia. The patients were examined using the international standards accepted for this disease. Results and discussion. 180 out of the 402 patients were treated in hospital; the others were examined during outpatient visits. The patients' mean age was 40.8±11.5 years; there were 292 (72.6%) men; 82.6% were HLA-B27 positive. The average age of onset was 27.6 years; the interval between symptom onset and diagnosis was 85.2 months. The rheumatologists  established the diagnosis in 87.3% of the cases. BASDAI and BASFI averaged 4.3±2.1 and 4.1±1.8, respectively. At the trial, there was peripheral arthritis in 33.1% of the patients, enthesitis in 37.1%, and dactylitis in 1.2%. Joint endoprosthesis was carried out in 4.7% of the patients. The most common  comorbidities were hypertension (25.1%), gastric ulcer (9.7%), coronary heart disease (4.0%), and diabetes mellitus (3.0%).Conclusion. AS is diagnosed in real practice more than 7 years after its onset mainly by rheumatologists.The delay of the diagnosis is mostly associated with the fact that specialists of other medical specialties are unaware of the clinical presentation  of the disease. The examined group of patients with AS shows a relatively high activity and obvious functional impairments, which is primarily related to the specific features of patient selection in this trial.